ANTI-CORRUPTION LEGISLATION IN VIETNAM: BARRIERS IN PRACTICAL APPLICATION - Bao Khanh Nguyen Huynh (JLAST : Journal of Law and Social Transformation, 2025)
Corruption has long been recognized as a persistent social phenomenon. Still, since the latter half of the twentieth century, it has increasingly manifested as a malignant global challenge, threatening not only economic growth but also cultural integrity and social morality. In many countries, corruption undermines the foundations of governance, erodes public trust, and obstructs sustainable development. This article provides an overview of the manifestations, scale, and detrimental consequences of corruption for social progress, with a specific focus on recent developments in Vietnam. Despite continuous policy efforts and institutional reforms, the author argues that the overall effectiveness of anti-corruption initiatives remains limited. The core problem lies in the insufficient intensity and comprehensiveness of current measures, which fail to generate transformative outcomes. Drawing on both theoretical perspectives and empirical observations, the article emphasizes that a breakthrough in anti-corruption requires a more rigorous approach—particularly through the consistent and strict punishment of corrupt individuals. The author highlights that sanctions should be applied impartially, with special attention to cases involving Party members and public officials, since their misconduct severely damages state credibility. By underlining the urgency of decisive legal enforcement, the study contributes to the broader discourse on strengthening the rule of law and enhancing the effectiveness of anti-corruption strategies in transitional societies.